Pengaruh Corporate Governance, Kualitas Laba, Ukuran Perusahaan Terhadap Asimetris Informasi - Dini Fadillah; Mayar Afriyenti (Universitas Negeri Padang, 2020)
This study aims to examine the effect of corporate governance, earnings quality and firm size on asymmetric information. The sample used in this study was a company registered in the corporate governance perception index (CGPI) in 2014-2018 with a sampling method that is purposive sampling, so a sample of 16 companies was obtained. This study uses multiple regression data analysis techniques by comparing the adjusted R-square of each model used. The results showed that adjusted R-square corporate governance on companies registered with CGPI had a significant negative effect on asymmetric information. While adjusted R-square earnings quality has no effect on asymmetric information and also firm size has no effect on asymmetric information